Estudo das propriedades estruturais e magnéticas de nanopartículas de CoO e CoO@MnFe2O4 - Freitas, Cintia Raquel Duarte de (2023)
Research with nanoparticles has been growing in the scientific environment because these nanoparticles result from the combination of materials with different properties, which allows us to envision applications of new properties and phenomena in different sectors of science and technology. In the case of bimagnetic core-shell nanoparticles, magnetic coupling effects at the interface affect the magnetization, anisotropy and coercivity of the starting materials, for example, and can contribute to obtaining nanoparticles with superior magnetic properties or directed towards a specific type of application. In this work we present a study on the synthesis methods, structural and magnetic characterization of CoO nanoparticles coated with MnFe2O4. The samples were prepared by the co-precipitation and ionic coordination reaction (RCI) method, with reduction of N2. Through structural and morphological characterization, we demonstrated the obtaining of nanostructures with pure phases. X-ray diffraction (XRD) results showed the formation of crystalline phases of CoO and MnFe2O4, all with cubic symmetry and space groups: Fm-3m and Fd-3m. The average diameter of the CoO core varied between 8 nm and 10 nm, and the thickness of the MnFe2O4 shell was ≈ 2 nm. Performing a broad experimental magnetic analysis, we evaluated the magnetic response for the CoO and MnFe2O4 phases, as well as for the core-shell nanostructure. Magnetic hysteresis cycle measurements at room temperature and at low temperature were made on the samples. For the CoO@ MnFe2O4 nanoparticles, magnetization measurements at low temperatures with different fields, the hysteresis cycles showed a displacement, an effect called “Exchange Bias”, in addition to an increase in coercivity. A detailed study was also carried out on CoO nanoparticles, with an average diameter of 8 nm. Zero Field Cooling (ZFC) and Field Cooling (FC) measurements showed a strong indication spin-glass behavior.